1993
DOI: 10.21273/hortsci.28.8.819
|View full text |Cite
|
Sign up to set email alerts
|

Treating `Primofiori' Lemons in Cold Storage with Intermittent Warming and Carbon Dioxide

Abstract: Several intermittent 13C warming treatments were applied to `Primofiori' lemons (Citrus limon Burn) stored at 2 or SC. Fruit stored at 13C were treated with 10%, 2090, or 30% CO2 for 24 hours at weekly intervals. Reduction in decay and physiological disorders was best with two cycles of 2 weeks at 2C and 2 weeks at 13C and relative humidity >95 %. Under this storage condition, soluble solids concentration, pH, titratable acidity, and reducing sugars di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The reduction of percent citric acid, at the end of storage, was previously recorded by El-Nawam (1991) on oranges; Cohen et al (1991); Angadi & Krishnamurthy (1992) on mandarins; El-Zayat et al (1998) on limes andEl-Wahab (2000) on "Washington Navel" oranges. However, Artes et al (1993) noticed that titratable acidity of "Primofiori" lemons was not changed relatively during storage.…”
Section: -Titratable Acidity (Ta)mentioning
confidence: 98%
See 1 more Smart Citation
“…The reduction of percent citric acid, at the end of storage, was previously recorded by El-Nawam (1991) on oranges; Cohen et al (1991); Angadi & Krishnamurthy (1992) on mandarins; El-Zayat et al (1998) on limes andEl-Wahab (2000) on "Washington Navel" oranges. However, Artes et al (1993) noticed that titratable acidity of "Primofiori" lemons was not changed relatively during storage.…”
Section: -Titratable Acidity (Ta)mentioning
confidence: 98%
“…The reduction of V.C content at the end of storage period, was previously reported by Al-Doori et al (1990) on "Mahaley" orange and Rana & Kartar (1992) on sweet oranges. However, Artes et al (1993) reported that the concentration of ascorbic acid in "Primofiori" lemons increased in relation to harvest values during storage.…”
Section: -Ascorbic Acid (Vc)mentioning
confidence: 98%
“…Fruit stored at 20°C were mostly infected with Phytophthora and Rhizopus. Artés et al (1993) speculated a close correlation between storage temperature and disorder development in lemon. They observed that lemons stored at 2°C were mainly infected by Alternaria citri, whereas those stored at 20°C were infected by Penicillium digitatum and P. italicum.…”
Section: Maturitymentioning
confidence: 99%